Protocol for semi‐automatic identification of whiteflies Bemisia tabaci and Trialeurodes vaporariorum on yellow sticky traps. (26th March 2019) - Moerkens, Rob; Brenard, Nathalie; Bosmans, Lien; Reybroeck, Eva; Janssen, Dirk; Hemming, Jochen; Sluydts, Vincent
Abstract: Yellow sticky traps (YSTs) are commonly used in greenhouse crops to monitor flying pest species. Whiteflies like Trialeurodes vaporariorum (Westwood) (Hemiptera: Aleyrodidae) and Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) are typically monitored using YSTs in tomato and sweet pepper crops. By counting the whiteflies on a YST, growers get an idea of the pests density in space and time in the greenhouse and can take pest control measurements accordingly. The downside is that manual counting of whiteflies on a YST is very time‐consuming and thus costly. A protocol to semi‐automate counting and identification of whiteflies on YSTs using image analysis software was developed to speed up the monitoring process. Bemisia tabaci is on average smaller than T. vaporariorum and by discriminating by size based on the amount of pixels in digital images, ratios of both species in a mixed population on YSTs could be estimated accurately. At low densities, the countings of different YSTs should be pooled till a 200 density threshold is reached in order to get accurate ratio estimates of both species. This study provides a protocol to reliably count and identify whiteflies semi‐automatically on standardized pictures. More research is required to develop alternative techniques to make standardized pictures in the field (e.g., with smartphone).